Effect of surface modification of SiO2 particles on the interfacial and mechanical properties of PBS composites. Issue 8 (15th June 2022) - Hou, Hongbo; Pu, Zejun; Wang, Xu; Zhu, Rongli; Li, Xianyong; Zhong, Jiachun
Abstract: In this study, WPU@SiO2 nanoparticles were obtained by grafting waterborne polyurethane (WPU) on the surface of silicon dioxide (SiO2 ). Then, WPU@SiO2 nanoparticles were introduced into the matrix of polybutylene succinate (PBS) to prepare a series of PBS/WPU@SiO2 composites. The dispersibility and interfacial compatibility of filler and matrix can be improved obviously by grafting a layer of WPU onto the surface of SiO2 nanoparticles. The FTIR and TGA results showed that WPU was successfully grafted onto the surface of SiO2 . According to polarizing microscope images, it is clear that the size of the pure PBS crystals is much larger than that of the PBS/WPU@SiO2, and a large number of crystals are evenly distributed in the PBS/WPU@SiO2 composite. In addition, DSC and TGA results indicated that PBS/WPU@SiO2 composite films show excellent thermal properties. Meanwhile, the initial thermal decomposition temperature of PBS/WPU@SiO2 composite films is about 366–374°C. For the 10 wt% WPU@SiO2 reinforced PBS‐based composite films, the tensile strength reached the ultimate value (38.49 MPa), which is 32.04% higher than that of pure PBS. Based on its excellent mechanical and thermal properties, the PBS/WPU@SiO2 composites have a broad application prospect in the field of biodegradable materials. Abstract : In this study, WPU@SiO2 nanoparticles were obtained by grafting waterborne polyurethane (WPU) on the surface of silicon dioxide (SiO2 ). Then, WPU@SiO2 nanoparticles were introduced into the matrix of polybutylene succinate (PBS) to prepare a series of PBS/WPU@SiO2 composites. For the 10 wt% WPU@SiO2 reinforced PBS‐based composite films, the tensile strength reached the ultimate value (38.49 MPa), which is 32.04% higher than that of pure PBS.